2006
DOI: 10.2190/bred-nrj7-3lv7-2qcg
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model of Work and Health Disparities in the United States

Abstract: Recent research in medicine and public health highlights differences in health related to race, ethnicity, socioeconomic status, and gender. These inequalities, often labeled "disparities," are pervasive and pertain to the major causes of morbidity, mortality, and lost life years. Often ignored in discussions of health disparities is the complex role of work, including not only occupational exposures and working conditions, but also benefits associated with work, effects of work on families and communities, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
197
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(207 citation statements)
references
References 91 publications
5
197
0
5
Order By: Relevance
“…Employment conditions have a major effect on health and health inequalities via social, economic, and physical pathways; work can be considered a direct determinant of health disparities (Benach, Muntaner, & Santana, 2007;Lipscomb, Loomis, McDonald, Argue, & Wing, 2006). Farmworkers suffer myriad health consequences of their work.…”
Section: Farmworker Health and Povertymentioning
confidence: 99%
“…Employment conditions have a major effect on health and health inequalities via social, economic, and physical pathways; work can be considered a direct determinant of health disparities (Benach, Muntaner, & Santana, 2007;Lipscomb, Loomis, McDonald, Argue, & Wing, 2006). Farmworkers suffer myriad health consequences of their work.…”
Section: Farmworker Health and Povertymentioning
confidence: 99%
“…1---4 Yet, despite a growing body of literature documenting numerous adverse impacts of low income status on health, 1,5,6 the issue of wage theft has been largely neglected in public health. Wage theft-or the nonpayment of wages and benefits to which workers are legally entitled-takes many forms, among them nonpayment of earned overtime, underpayment of the minimum wage, delayed or nonpayment of back wages, misclassification of employees as independent contractors, confiscation of tip money, and failure to grant mandated breaks or paid sick leave.…”
Section: /Ajph2013301813)mentioning
confidence: 99%
“…A number of researchers have documented the workforce segmentation that has historically been the lot of racial and ethnic minorities within the United States, and that now often relegates Latino workers both to the highest risk sectors, and to the hardest job assignments within a workplace [Anderson et al, 2000;Lipscomb et al, 2006;Friedman and Forst, 2008;Marin et al, 2009]. For unauthorized workers, immigration status can be a potent source of potential abuse and exploitation by supervisors that may, in fact, contribute to more accidents.…”
Section: Immigrant Workers and Workforce Segmentationmentioning
confidence: 99%
“…These include a lack of understanding of workers' compensation coverage, and lack of ability to communicate in English [Lashuay and Harrison, 2006]. Workers' lack of understanding of the legal system and lack of union membership, only exacerbate the willingness of some employers to fire vulnerable workers [Lipscomb et al, 2006]. A study of even unionized, largely immigrant hotel workers found that only 20 percent of those who had experienced work-related pain had filed workers' compensation claims, for fear of getting ''in trouble'' or being fired [Scherzer et al, 2005].…”
Section: Barriers To Filing Of Workers' Compensation Claims For Immigmentioning
confidence: 99%